Spiritual Leadership in Forming Quranic Character Through the Quran Tahfiz Program - Ningrum, Aning Puspita; Na'imah; Jati , Rasi A’yun Andhini; Samosir, Nurul Aisah; Nihayatuzzain, Nihayatuzzain (Journal of Innovation and Research in Primary Education, 2025)
This study aims to describe the application of spiritual leadership in the Quran memorization (tahfiz) program and the extent to which this program contributes to the formation of students’ Quranic character. The research was conducted at MI Al-Islamiyah Grojogan, Bantul, Yogyakarta, over one month in June 2025. Using a qualitative case study approach, data were collected through observation, documentation, and in-depth interviews with 3 teachers and 1 principal, then analyzed using the Miles and Huberman interactive model, including data reduction, presentation, and conclusion drawing. The results show that the principal plays a central role in creating an Islamic value-oriented learning environment, not only through administrative policies but also by serving as a consistent moral and spiritual role model. The implementation of spiritual leadership is reflected in support for the tahfiz program, active involvement in religious activities, and ongoing character development. Furthermore, synergy between the principal, tahfiz teachers, and students contributes to the establishment of a strong religious culture in which Quranic values are both taught and internalized through daily practice. However, challenges remain, particularly regarding family support and balancing academic learning with character education. Therefore, it is recommended that schools strengthen teacher training in spiritual leadership, integrate tahfiz activities more systematically with character education, and build sustainable collaboration with parents and the wider community to optimize the internalization of Quranic values.